Stock Market Volatility And Presidential Election Uncertainty: Evidence From Political Futures Markets - Bowes, David R. (Journal of Applied Business Research, 2017)
Uncertainty about the economy can increase volatility in financial market returns. One potential source of uncertainty is the outcome of an upcoming national election. This paper uses a GARCH model to estimate the effect of uncertainty surrounding U.S. Presidential elections on the volatility of U.S. stock market returns from 1992-2012. Uncertainty in these elections is measured using asset prices from the Iowa Electronic Market (IEM), an on-line futures market based on real-world events, including U.S. elections. The empirical results show that the conditional variance in S&P 500 returns increases when IEM presidential election futures market asset prices indicate greater uncertainty about the outcome of an upcoming election.
Keywords: Stock Market; Election; GARCH; Iowa Electronic Market; Volatility; Efficient Market Hypothesis